Evidence to Support the Collaboration of SP1, MYC, and HIF1A and Their Association with microRNAs - Jong Ho Chun; Kotohiko Kimura; Monika Rajput; Ming-Hua Hsu; Yu-Chuan Liang; Akanksha Ramadas Shanbhag; Pei-Ju Chiang; Tiffany L. B. Jackson; Ru Chih C. Huang (Current Issues in Molecular Biology)
This study provides evidence to support the concept proposed by Kimura et al. in 2023 that the inhibitors of SP1, MYC, and HIF1A should induce strong anticancer activity by reducing the expression of stem cell-related proteins. In LN229 and U87MG glioblastoma cells, either tetra-methyl-O-nordihydroguaiaretic acid (M4N) or tetra-acetyl-O-nordihydroguaiaretic acid (A4N) suppressed SP1 and only a few stem cell-related proteins and induced only a small amount of cell death; in contrast, the combination treatment of M4N with A4N greatly suppressed the expression of SP1, MYC, and HIF1A, as well as all of the stem cell-related proteins examined, and greatly induced cell death. The bioinformatic analysis showed that the proteins associated with SP1, MYC, and HIF1A were specifically involved in the regulation of transcription and that various microRNAs (miRNAs) that had been shown to induce either anti- or procancer activity were associated with SP1, MYC, and HIF1A, which suggested that the inhibition of SP1, MYC, and HIF1A could modulate the transcription of both coding and noncoding RNAs and affect cancers. These data overall supported our concept.